2022
DOI: 10.1021/acsphotonics.2c00041
|View full text |Cite
|
Sign up to set email alerts
|

Bright Future of Deep-Ultraviolet Photonics: Emerging UVC Chip-Scale Light-Source Technology Platforms, Benchmarking, Challenges, and Outlook for UV Disinfection

Abstract: The COVID-19 pandemic has generated great interest in ultraviolet (UV) disinfection, particularly for air disinfection. Although UV disinfection was discovered close to 90 years ago, only very recently has it reached the consumer market and achieved much acceptance from the public, starting in the 2000s. The current UV light source of choice has been almost exclusively a low-pressure mercury vapor discharge lamp. Today, however, with emerging deep-UV (DUV) chip-scale technologies, there has been a significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 54 publications
(91 reference statements)
0
21
0
1
Order By: Relevance
“…The interest toward deep-ultraviolet (UV) phosphors has recently tremendously grown in view of their potential utilization in tri-band-based light-emitting diodes (LEDs) for biochemical and medical applications. In particular, these materials can be used as so-called C, B, or A UV emission devices for catalyst and sterilization, whereas it has been shown that the sources operating in the C-UV range of 280–200 nm are preferred due to the most efficient germicidal effect. , Although rare-earth dopants in phosphors are the most widely used by now, the depletion of natural resources has driven the research efforts to the development of rare-earth-free substitutes suitable for emerging applications. These application needs have risen the issue of suitable materials.…”
Section: Introductionmentioning
confidence: 99%
“…The interest toward deep-ultraviolet (UV) phosphors has recently tremendously grown in view of their potential utilization in tri-band-based light-emitting diodes (LEDs) for biochemical and medical applications. In particular, these materials can be used as so-called C, B, or A UV emission devices for catalyst and sterilization, whereas it has been shown that the sources operating in the C-UV range of 280–200 nm are preferred due to the most efficient germicidal effect. , Although rare-earth dopants in phosphors are the most widely used by now, the depletion of natural resources has driven the research efforts to the development of rare-earth-free substitutes suitable for emerging applications. These application needs have risen the issue of suitable materials.…”
Section: Introductionmentioning
confidence: 99%
“…As of 2020, the highest WPE achieved for a commercially available 280 nm UV LED was 4.1% (LP lamps 30-35%) and equivalent quantum e ciency (EQE) was 6.1% 28 . Currently, UV LEDs in the 280 nm ± 5 nm range have an EQE ranging from 9-20.3% 7,29 and best LEDs would typically be around 7.1%. This marked improvement in the last few years, and forecasted improvements for UV LED WPE indicate that the energy e ciency discrepancy will decrease as LED light sources improve 30,31 .…”
Section: Energy Implicationsmentioning
confidence: 99%
“…Understanding how to scale and build climate responsive technologies is key in ful lling the intersection of SDG6 and SDG13, Climate Action, in a timely manner. UV light emitting diodes (LEDs) address the previously mentioned drawbacks of conventional wastewater UV disinfection, while providing a climate responsive solution [6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…For example, UVC light below 280 nm wavelength has a strong biocidal effect against protozoa, bacteria, viruses, and molds, destroying or inactivating microorganisms so that they can no longer multiply. Light at wavelengths near 265 nm is the most effective for producing this effect [ 1 , 2 ]. Light at 280 nm wavelength and below is also needed for non-line-of-sight urban communication applications [ 3 ] and can be potentially used in deep UV lithography.…”
Section: Introductionmentioning
confidence: 99%
“…Light at 280 nm wavelength and below is also needed for non-line-of-sight urban communication applications [ 3 ] and can be potentially used in deep UV lithography. UVC light is crucial for applications including the safeguarding of mobile and stationary water supplies, mobile water purification facilities, general municipal water treatment, the treatment of public and private swimming facilities, air treatment of enclosed facilities, and biomedical sanitation [ 2 , 4 ]. It has been recently shown that skin disinfection by UV radiation with wavelengths shorter than 240 nm is much more attractive than radiation in the range of 250–280 nm, since it is mainly absorbed in the upper non-living layer of the skin [ 5 ].…”
Section: Introductionmentioning
confidence: 99%